Stakeholder Participation and Project Sustainability: A Case of Deaf Donor Funded Project in Kicukiro, Rwanda - Uwamariya, Alexia; Safari, Ernest; Kengere, Osiemo A. (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2021)
Researches has shown that due to less participation of stakeholders in project sustainability, most of donor funded projects fail or get stuck just after withdrawal of funds by donors. Hence, the purpose of this study of assessing the contribution of stakeholder’s participation in promoting project sustainability with a case study of Deaf Donor Funded Project in Kicukiro. The researcher used descriptive research design to a target population of 246 people in which 152 respondents’ were chosen using the formula of Yamane (1967) with census and purposive sampling techniques. The questionnaires were distributed to the respondents because the researcher did self – administration of questionnaires while collecting data, but a sign language translator was hired to help capture all the necessary information. The analysis of the questionnaire was done through use of SPSS version 21.0 hence the use of descriptive, regression and correlation tables within this study about participation of stakeholders and project sustainability. The findings also prove that there is a relationship between Skills and Ownership (p=.851 and sig=.000), between skills and continuation (p=.786 and sig=.000), between material and effective leader (p=.899 and sig=.000) because all calculated p- values are less than 0.01 level of significance.